2003
DOI: 10.1097/01.ccm.0000069538.12447.82
|View full text |Cite
|
Sign up to set email alerts
|

Stroke volumes and end-tidal carbon dioxide generated by precordial compression during ventricular fibrillation

Abstract: We confirmed that precordial compression produces approximately one third of prearrest stroke volumes during cardiopulmonary resuscitation and demonstrated that end-tidal carbon dioxide was quantitatively predictive of stroke volume index estimated by transesophageal echocardiographic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 53 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…The relationship between CO and partial end-tidal CO 2 pressure (PETCO 2 ) has been known for decades [13,14], so measurement of PETCO 2 has been proposed to confirm the restoration of spontaneous circulation in patients with cardiac arrest [15], but also as a quantitative indicator of hemodynamic effectiveness of precordial compression during cardiopulmonary resuscitation [16]. Moreover, since PETCO 2 is mainly determined by tissue CO 2 production (VCO 2 ), alveolar ventilation and CO (that is, pulmonary blood flow) [17], when stable metabolic conditions are assumed and minute ventilation is kept constant, acute changes in PETCO 2 have been shown to correlate strongly with changes in CO in experimental [18-24] and clinical [25,26] settings.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CO and partial end-tidal CO 2 pressure (PETCO 2 ) has been known for decades [13,14], so measurement of PETCO 2 has been proposed to confirm the restoration of spontaneous circulation in patients with cardiac arrest [15], but also as a quantitative indicator of hemodynamic effectiveness of precordial compression during cardiopulmonary resuscitation [16]. Moreover, since PETCO 2 is mainly determined by tissue CO 2 production (VCO 2 ), alveolar ventilation and CO (that is, pulmonary blood flow) [17], when stable metabolic conditions are assumed and minute ventilation is kept constant, acute changes in PETCO 2 have been shown to correlate strongly with changes in CO in experimental [18-24] and clinical [25,26] settings.…”
Section: Introductionmentioning
confidence: 99%
“…Until then, several authors had studied the effect of chest compression on ETCO 2 [24][25][26][27]. This non-invasive, indirect, quantitative technique may serve as an indicator of systemic and pulmonary circulation during CPR and can reflect its effect on cardiac output and stroke volume index [28][29][30][31][32].…”
Section: Effectiveness Of Chest Compressionsmentioning
confidence: 99%
“…It has previously been concluded that EtCO 2 correlates well with blood flow and that PLR induces an increase in descending aortic blood flow of at least 10% or in echocardiographic sub-aortic flow of at least 12% [23-26]. In other studies, EtCO 2 has been shown to be quantitatively predictive of stroke volumes [27]. EtCO 2 has also been described as an important value for predicting ROSC and CPR quality [22,28,29].…”
Section: Introductionmentioning
confidence: 99%